2012
DOI: 10.1038/pj.2012.211
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis and addition polymerization of novel Me3Si- and Me3Ge-substituted tricyclononenes

Abstract: Addition and ring-opening metathesis polymerizations of new monomers (Me 3 Si-and Me 3 Ge-substituted tricyclononene and tricyclononadienes) were studied. Addition polymerization was carried out on Pd-and Ni-catalyst systems activated by B(C 6 F 5) 3 and/or methylalumoxane. New addition polymers were obtained with good yields up to 70% and with molecular weights (M w) up to 5.6 Â 10 5. Metathesis polymerization was performed using the first-generation Grubbs catalyst. The yields of the first obtained metathesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…It was shown that addition type polynorbornenes are more permeable than metathesis polymers but the latter are more readily obtained due to the high driving force of metathesis polymerization of high strain norbornene monomers . High gas permeability level of these polymers was caused by the presence of spherical bulky groups (e.g., trimethylsilyl groups or trimethylgermyl groups) and rigid polymer chains which disrupt a dense polymer chain package . Bulky SiMe 3 groups were also introduced into other classes of polymers (polyacetylenes, polystyrenes, polysulfones, poly(phenylene oxide), polyolefins).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that addition type polynorbornenes are more permeable than metathesis polymers but the latter are more readily obtained due to the high driving force of metathesis polymerization of high strain norbornene monomers . High gas permeability level of these polymers was caused by the presence of spherical bulky groups (e.g., trimethylsilyl groups or trimethylgermyl groups) and rigid polymer chains which disrupt a dense polymer chain package . Bulky SiMe 3 groups were also introduced into other classes of polymers (polyacetylenes, polystyrenes, polysulfones, poly(phenylene oxide), polyolefins).…”
Section: Introductionmentioning
confidence: 99%
“…In general, ROMP polymerization of tricyclononenes proceeds readily due to a high strain energy of the norbornene fragment and the exo ‐orientation of cyclobutane ring . Earlier we have demonstrated that ROMP polymerization of tricyclononenes and tricyclononadienes proceeds effectively in the presence of the 1st generation Grubbs catalyst at high monomer/catalyst ratios resulting in high molecular weight polymers. This process is characterized by a good reproducibility and tolerance to the strain cyclobutene ring in the case of polymerization of tricyclononadienes .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier we have demonstrated that ROMP polymerization of tricyclononenes and tricyclononadienes proceeds effectively in the presence of the 1st generation Grubbs catalyst at high monomer/catalyst ratios resulting in high molecular weight polymers. This process is characterized by a good reproducibility and tolerance to the strain cyclobutene ring in the case of polymerization of tricyclononadienes . So all the polymers studied in this work were synthesized on the above catalyst according to Scheme (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that among norbornene derevatives exo-tricyclononenes were more attractive due to their enhanced activities in polymerization [5][6][7][8][9]. We have demonstrated previously that quadricyclane (Q) entered into [2σ + 2σ + 2π] stereoand regiospecific cycloaddition reaction with silicon-and germanium-substituted ethylenes and acetylenes resulting in a formation of substituted tricyclo[4.2.1.0 2,5 ]nonenes and tricyclo[4.2.1.0 2,5 ]nonadienes [7,[10][11][12][13]. Methylation of these cycloadducts led to highly active monomers.…”
Section: Introductionmentioning
confidence: 97%